RELOKASI ANGGARAN PENDIDIKAN DALAM PROGRAM MAKAN BERGIZI GRATIS DAN REPRODUKSI KETIDAKSETARAAN SOSIAL DALAM PERSPEKTIF PIERRE BOURDIEU - Rahmatia Utami, Delfira; Rizki Febrianti, Nur; Locita Salsabila, Galuh; Utami, Mita; Pratiwi, Utami; Kurniawan, Rudy (STKIP Subang, 2026)
This study aims to analyze the reallocation of education funding in the implementation of the Free Nutritious Meal Program (MBG) and its implications for the reproduction of social inequality from Pierre Bourdieu’s perspective. Education, as a social field, is not a neutral space but an arena in which various forms of capital compete and shape opportunities for social mobility. The reallocation of education budgets to support the MBG program raises fiscal trade-offs that may weaken the emancipatory function of education, particularly for groups that rely heavily on public education services. This research employs a descriptive qualitative method through a literature study of policy documents, official reports, and relevant academic studies. The findings indicate that although the MBG program aims to improve human capital through nutritional interventions, the reallocation of education funding may exacerbate inequalities in the distribution of economic, cultural, social, and symbolic capital within the educational field. Such conditions potentially reinforce mechanisms of social reproduction through habitus and symbolic violence that operate subtly within the education system. Therefore, human development policies should be designed in a complementary manner to ensure that nutritional interventions do not undermine long-term investments in educational quality and equity.